Assessing physical activity promotion in different settings and how its associated with public participation during COVID-19 epidemic: evidence from national policy evaluation - Narakorn Wongsingha; Dyah Anantalia Widyastari; Burathep Chokthananukoon; Niramon Rasri; Piyawat Katewongsa (BMC, 2023)
Abstract Background Various interventions, programs and policies have been implemented to improve physical activity (PA) levels worldwide. However, countries continue to face barriers and challenges in achieving their targets. To date, there is a lack of study on the evaluation of physical activity (PA) promotion and how it's associated with public participation. Methods This study assessed PA promotion in eight different settings in terms of policy availability, policy implementation, and public participation in PA programs. Policy availability was assessed by reviewing 384 policy and strategy documents, rules, regulations, legislation, and guidelines on PA. We scored the documents by using the Comprehensive Analysis of Policy on Physical Activity (CAPPA) framework. Data to assess policy implementation and public participation were taken from the Thailand Report Card Survey 2021 (TRC2021), and the Thailand Surveillance on Physical Activity (SPA) 2021. Both surveys comprised over 5,000 nationally-representative samples from on-screen, face-to-face interviews, and an online self-administered survey. We scored the policy implementation and public participation based on respondents' response towards policy implementation and participation indicators. A grading scheme was applied to indicate how successful an investment has been made. Results Public education and mass media received the highest average score in policy availability, implementation and public participation in PA program (67.9%, grade B), followed by active urban design (66.1%, grade B-) and active transport (63.7%, grade B-). Workplace, whole-of-school, and community-wide initiatives were the investments with the lowest scores, implying low availability, limited implementation, and less accessibility to public. Females were less likely to participate in active transport, active urban design, sports/recreation for all, workplace activity, and community-wide initiatives. Age and educational attainment were consistent predictors of utilization in all investments. Conclusions With varying degrees of policy availability and accessibility, public participation in PA investments is likely to be constrained by biological and socioeconomic inequality. Future investments should aim at providing generalized or tailored interventions to ensure equal access and participation for all segments of the population.